Leaving Home: How Older Adults Prepare for Intensive Volunteering. (March 2015) - Cheek, Cheryl; Piercy, Kathleen W.; Grainger, Sarah
Using the concepts in the Fogg Behavioral Model, 37 volunteers aged 50 and older described their preparation for intensive volunteering with faith-based organizations. Their multistage preparation process included decision points where respondents needed to choose whether to drop out or continue preparation. Ability was a stronger determinant of serving than motivation, particularly in terms of health and finances. This model can facilitate understanding of the barriers to volunteering and aid organizations in tailoring support at crucial points for potential older volunteers in intensive service.